PENGARUH PROFITABILITAS, OPINI AUDITOR, UKURAN PERUSAHAAN, DAN UKURAN KAP TERHADAP AUDIT DELAY (Studi Empiris pada Perusahaan Pertambangan Yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2020) - Lilis Indrawati; Suyatmin Waskito Adi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the effect of profitability, auditor opinion, company size, KAP size on audit delay. The population in this study is mining companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020. The data used is taken from the financial statements of mining companies for 2017-2020. The sample in this study was determined by purposive sampling method, so that the sample that met the criteria for taking the sample in this study were 19 companies. The data analysis model used is multiple linear regression model. The results of this study indicate that KAP size influences audit delay, while profitability, auditor opinion, company size have no effect on audit delay.